Entre el discurso modernizador y la propaganda hispanista. Instrumentos y posibilidades de la dimensión cultural de las relaciones hispano-brasileñas (1950-1960) (Res Gesta, 2018)
The aim of this paper is to discuss the cultural dimension of Spanish- Brazilian relations in the 1950s. Intend to analyze the cultural diplomacy actions taken by Brazil and Spain, showing how they fit within the context and the main objectives of foreign policy both countries.
Keywords: Cultural diplomacy; Foreign policy; Franquismo; Itamaraty